2011
DOI: 10.1074/jbc.m111.290114
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of a PNPLA3 Protein Isoform (I148M) Associated with Nonalcoholic Fatty Liver Disease

Abstract: Background: A genetic variant of PNPLA3 (I148M), an enzyme of unknown function, confers susceptibility to fatty liver disease.Results: Purified human PNPLA3 catalyzed hydrolysis of glycerolipids with a preference for oleoyl esters; the I148M substitution substantially decreased hydrolytic activity.Conclusion: PNPLA3 catalyzes hydrolysis rather than synthesis of triacylglycerol.Significance: PNPLA3-I148M impairs hydrolytic activity against multiple glycerolipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
273
2
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(315 citation statements)
references
References 23 publications
(40 reference statements)
20
273
2
3
Order By: Relevance
“…PNPLA3 exhibits predominantly hydrolase (lipase) activity in vitro against triglycerides (TG) and retinyl esters in hepatic stellate cells [76,[78][79][80] (Fig. 1).…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…PNPLA3 exhibits predominantly hydrolase (lipase) activity in vitro against triglycerides (TG) and retinyl esters in hepatic stellate cells [76,[78][79][80] (Fig. 1).…”
Section: Reviewmentioning
confidence: 99%
“…1). Among TG, PNPLA3 has a higher enzymatic activity against those containing monounsaturated and polyunsaturated fatty acids [78,81].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies using recombinant purified human PNPLA3 have shown that the wild-type enzyme hydrolyzes triglycerides and that the I148M substitution abolishes this activity (9). These data suggested that the I148M substitution is a loss-of-function mutation impairing triglyceride hydrolysis.…”
Section: IImentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) in the PNPLA3 gene, i.e., rs738409 C>G, results in an amino acid exchange from isoleucin to methionine at position I148M of PNPLA3 2. This common variant represents a missense mutation associated with a loss‐of‐function of the hydrolase activity of the enzyme, promoting triglyceride accumulation in hepatocytes, impaired retinol synthesis in hepatic stellate cells, formation of larger lipid droplets, and reduced secretion of triglyceride‐rich very low‐density lipoprotein (VLDL) both in vitro and in vivo (reviewed in Trepo et al5).…”
mentioning
confidence: 99%